Educação ambiental e a pedagogia Waldorf: estudo comparativo do processo de ambientalização da educação em três escolas em diálogo com os princípios Steinernianos - Ziegler, Sandra Sylvia (2017)
Nowadays we find ourselves in a scenario of environmental crisis, generated by human action, life starts to be considered from the market laws, and from economic and technological order, producing a mechanistic and linear thinking that fractures the world, ignores the diversity in its interfaces and subjugates the traditional knowledge of Humanity to scientific knowledge. In the midst of this scenario, it is necessary that we have the notion of how pertinent is to create possibilities of educating individuals turning to the development of a thinking and acting with autonomy and capable to confront the various contemporary crises that afflict us. This time we are in validate the emergence of this objective in which the world and societies needs to pursue. In this context, this study aimed to promote the educational dialogue between different conceptions and pedagogical practices related to the socioenvironmental issue, aiming mutual enrichment of the experiences and principles observed in three schools. Our research focused on three schools, namely: one private, the Instituto de Educação Integrada (IPEI), another public, the Centro Estadual Experimental de Ensino Aprendizagem Sesquicentenário (CEEEAS), both in the municipality of João Pessoa, state of Paraíba, and another associative, School Waldorf Rural Dendê da Serra (EWRDS), in the village of Serra Grande, in the municipality of Uruçuca, Bahia. In order to carry out this study we opted for qualitative research based on ethnographic approach through observations and subjective emphasis on the motives and perceptions that the actors adopt to look and act on the world. To collect data, we used systematic observations of school daily life, and documentary analysis of secondary data such as the Political-Pedagogical Project and School Plans, and semi-structured interview with teachers, education specialist, students and employees of the investigated schools. The data analysis was constructed from the selection, organization and classification of the material in thematic nuclei made up of key-ideas that allowed a free interpretation from the theory developed in the referential. From the data presented, we observed similarities in two schools regarding methodology and theoretical and practical pedagogical conceptions in the process of environmental education, which are presented in a different perspective in relation to the third school. Therefore, it is understood that the Waldorf Pedagogy in its principles and foundations given its holistic, systemic, intertrans-multidisciplinary and complex perspective, can contribute in a relevant way to the insertion of the environmental issue in education.